PENGARUH METODE COURSE RIVIEW HORAY TERHADAP HASIL BELAJAR SISWA KELAS VIII DALAM PEMBELAJARAN PAI DI SMP AL AZHAR MUNCAR - Mashuri, Imam; Erlangga, Moh; Lestari, Diana (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
Study this aim for knowing there is influence in increase results study students. Background behind problem based on results observations made _ researcher at Al-Azhar Muncar. Middle School use method modern learning still seldom used in the learning process. This thing result in results study student experience slight increase. _ Based on problem the need existence change in delivery PAI material for results study siawa the more increase. Formulas problem in study this is is there is Influence Method Course Review Horay Against Learning Outcomes Class VIII Students in PAI Learning at Al-Azhar Muncar Middle School Academic Year 2021/2022 and how much big there is Influence Method Course Review Horay Against Learning Outcomes Class VIII Students in PAI Learning at Al-Azhar Muncar Middle School Academic Year 2021/2022. Type research used _ in study this is study quantitative. Type research used _ in study this is Quasy Experimental design. Population taken _ is whole class VIII SMP Al-Azhar Muncar whereas sample in study this is class VIII.A as class control no there is treatment and class VIII.B as class experiment. As for technique taking sample in study this is technique Cluster Sampling (sample group). Data analysis techniques in study this is a prerequisite test includes normality test and homogeneity test, T- test and large influence use method Courses Review Horay. Based on results study show that T- test results could is known the value of “Mean Difference” is of -10.5333. This value show difference between the average results study students in group A with average results study students in group B or 76.000-86.5333 = -10.5333 and the difference difference the is -14.5502 to -6.5164.